Analisis Penggunaan Kata Mubazir Teks PengalamanPribadi Karangan Siswa Kelas Vii SMP - Arti, Wini, Prof. Dr. Abdul Ngalim M.M, M.Hum (2017)
Garland students i.e. bouquet which is done in writing by students accompanied the aspect that in accordance with the rules of the spelling language is enhanced so that Indonesia produce a bouquet that is right and good. Sentences containing the word redundant is an excessive sentence does not save money and waste. This research has two goals. This research has two purposes (1) To identify the form of the use of the word redundant on writing personal experience in grade VII E, D Junior High School N 7 Sukoharjo. (1) Identify the use of the word redundant in writing personal experience on the students of class VII E, D JUNIOR N 7 Sukoharjo. (1)Sets forth the form of analysis of the words that are having to use the word redundant in the writing of personal experiences in grade VII junior high school. (2) Describes the form of word analysis which experiences the use of the word redundant in writing personal experience in the seventh grade students of junior high school type of research uses descriptive qualitative research methods. This research uses descriptive qualitative research method. Data from this research in the form of a personal experience essay students. The data from this research is in the form of the personal experiences of students. The method of data collection is done by the method refer to proceed with the technical note. Technique of data collecting done by method of refer to continue with the technique of note. Techniques of data analysis is done using the method of agih Data analysis technique is done by using the method of agih. The results of this research found a form of the word redundant include: The results of this study found the form of redundant words, among others: 1 essay containing waste of words which, in the words of waste 1, 2 containing the copula, 5 data contain two or more words that are synonymous, 6 contain the data, data contain pleonasme 10.